Causes of failure of pneumatic retinopexy - Roberto E. Flaminiano, MD; Robert T. Sy, MD; Milagros H. Arroyo, MD; Pearl Tamesis-Villalon, MD (Philippine Journal of Ophthalmology)
Objective: To determine the causes of failure in eyes that underwent pneumatic retinopexy at the University of the Philippines-Philippine General Hospital (UP-PGH).